Distance and near visual performance in pseudophakic eyes with simulated spherical and astigmatic blur. (3rd February 2016) - Serra, Pedro; Chisholm, Catharine; Sanchez Trancon, Angel; Cox, Michael
Abstract : Purpose: Increased depth‐of‐focus after cataract surgery is dependent on various ocular characteristics, including refractive astigmatism. This work studied the influence of meridional blur produced by astigmatism, and spherical blur, on distance and near visual performance in pseudophakic eyes. Methods: Visual performance was assessed monocularly in 59 pseudophakes (mean ± standard deviation, 66.9 ± 7.53 years) at distance (3.0 m) and near (0.33 m) using high‐ (HC: 94%) and low‐contrast (LC: 10%) visual acuity (VA) charts. Reading performance (maximum reading speed [MRS], threshold print size [TPS] and reading acuity [RA]) was evaluated at near using a reading chart. Four refractive conditions at distance and near were monocularly simulated using the following trial lenses: distance (in‐focus: ± 0.00 DS, with‐the‐rule [WTR] astigmatism: +2.00 × 180; against‐the‐rule [ATR] astigmatism: +2.00 × 90; spherical defocus: +1.00 DS) and near (in‐focus: +3.00 DS, WTR astigmatism: +2.00 × 180; ATR astigmatism: +2.00 × 90, spherical blur: ±0.00 DS). Results: Distance high‐ and low‐contrast VA were degraded by spherical and astigmatic blur in comparison to the distance in‐focus condition (p < 0.001 for all), with astigmatism in either of the forms being more harmful than spherical blur (p < 0.001 for all). At near, best HC‐ and LCVA were attained with full near correction (p < 0.001 for all) followed by the ATR and WTR astigmatism. For all conditions, the VA measured was independent of whether the astigmatism was WTR or ATR. However, MRS was higher with +3.00 DS and ATR astigmatism compared to the other conditions. RA and TPS significantly strengthened the weak pattern seen with HCVA at near, with ATR astigmatism allowing significantly better RA and TPS than WTR astigmatism (p < 0.001 for all). Conclusions: Simple myopic astigmatism improved near visual performance in pseudophakic eyes at the expense of some deterioration in distance performance. ATR astigmatism degraded VA at distance marginally more than WTR astigmatism and provided a marginally better VA at near. However, the benefit at near was more explicit when measured by reading performance, confirming the role of blur orientation on visual performance.